2014
DOI: 10.1523/jneurosci.0814-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Potentiation in Hilar Circuitry Modulates Gating by the Dentate Gyrus

Abstract: The dentate gyrus serves as a gateway to the hippocampus, filtering and processing sensory inputs as an animal explores its environment. The hilus occupies a strategic position within the dentate gyrus from which it can play a pivotal role in these functions. Inputs from dentate granule cells converge on the hilus, and excitatory hilar mossy cells redistribute these signals back to granule cells to transform a pattern of cortical input into a new pattern of output to the hippocampal CA3 region. Using voltage-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 38 publications
2
16
0
Order By: Relevance
“…Thus, most reports of excitatory effects of MCs on GCs have used recordings of GCs in slices where single cell recording or other methods are available that are difficult in vivo (Jackson and Scharfman, 1996;Chancey et al, 2014;Wright and Jackson, 2014;Hsu et al, 2015;Hashimotodani et al, 2017). On the other hand, MC-mediated inhibition of GCs in vivo is often judged only on inhibition of PP-induced GC population spikes (Sloviter, 1991;Jinde et al, 2012).…”
Section: The Net Effect Of Mcs On Gcsmentioning
confidence: 99%
“…Thus, most reports of excitatory effects of MCs on GCs have used recordings of GCs in slices where single cell recording or other methods are available that are difficult in vivo (Jackson and Scharfman, 1996;Chancey et al, 2014;Wright and Jackson, 2014;Hsu et al, 2015;Hashimotodani et al, 2017). On the other hand, MC-mediated inhibition of GCs in vivo is often judged only on inhibition of PP-induced GC population spikes (Sloviter, 1991;Jinde et al, 2012).…”
Section: The Net Effect Of Mcs On Gcsmentioning
confidence: 99%
“…Another in vivo study showed that induction of PP-GC LTP leads to LTP of contralateral MC-GC synapses (Alvarez-Salvado et al, 2013). Using voltage imaging in hippocampal slices, it has been reported that LTP of the GC-MC-GC loop can facilitate LTP at PP-GC synapses and by this way enable information transfer from entorhinal cortex to the CA3 area (Wright and Jackson, 2014). It is therefore possible that induction of PP-GC LTP in vivo, presumably by increasing MC activity via GCs, facilitates the induction of MC-GC LTP.…”
Section: Discussionmentioning
confidence: 99%
“…A follow-up study demonstrated NMDAR-dependent LTP of the ipsilateral associational path (Hetherington et al, 1994). Presumably based on these early studies, it has been commonly assumed that MC-GC synapses express classical NMDAR-dependent, Hebbian LTP (Lisman, 1999; Wright and Jackson, 2014), although this possibility was never directly tested in vitro. Here, we report that MC-GC synapses express a presynaptic form of LTP whose induction does not require NMDAR activation.…”
Section: Discussionmentioning
confidence: 99%
“…However, when the postsynaptic granule cell was depolarized, the effects of presynaptic mossy cell input were larger; thus, mossy cells can have a robust excitatory effect on depolarized granule cells 54 . Additional studies using approaches that lesioned mossy cells or the molecular layer in hippocampal slices 56,57,58 provided further evidence that mossy cells excite granule cells.…”
Section: Mossy Cell Function In the Dentate Gyrusmentioning
confidence: 95%
“…However, other methods have also shown that mossy cells may facilitate or even be required for LTP of the perforant path input to granule cells. Voltage imaging in hippocampal slices showed that the granule cell–mossy cell–granule cell circuit was necessary for perforant path–granule cell LTP 58 . Furthermore, it was shown that the expression of growth-associated protein 43 (GAP43; also known as neuromodulin) was increased in mossy cells in response to high-frequency stimulation of the perforant path, which could support the persistence of LTP 71 .…”
Section: Mossy Cell Function In the Dentate Gyrusmentioning
confidence: 99%